„Das Leben als Theater”. Afisze niemieckiego Teatru Miejskiego w Poznaniu w zbiorach Biblioteki Raczyńskich - Agnieszka Urbańska (Biblioteka)
The article examines eighteenth and nineteenth century posters produced or commissioned by the German Municipal Theatre in Poznań (then German Posen) that have been preserved in the collections of the Raczyński Library. The posters under scrutiny here were issued between 1789-1867. The sheer time span of this continuously documented history of Poznań theatre makes it possible to carry out an analysis of the changing repertoire of staged plays, actors’ staff members and art leaders, but also that of the pattern for the theatrical posters, graphical elements or the material used for their production. The article aims at presenting the function and the role of the aforementioned factors in the then theatre life of the multicultured Poznań as well as the meaning and significance of the theatre in the town itself.